Extensive thoracoscopic mediastinal lymph node dissection on the left side: how it should be done - Heineman, David J.; van Berge Henegouwen, Mark I. (Journal of Thoracic Disease, 2019)
Mediastinal lymph node dissection by video-assisted thoracic surgery (VATS) remains a challenging procedure. The authors describe their technique for a complete thoracoscopic mediastinal lymph node dissection of the left side. They righteously state in the introduction that there were worries in the past when VATS was introduced regarding the extent and quality of the mediastinal lymph node dissection.